GAME-BASED TEACHING METHODS OF BALLROOM DANCING FOR CHILDREN 3-4 YEARS OLD - Kazko, Dmytro (European Journal of Interdisciplinary Issues, 2025)
Early education of children of younger preschool age through movement and play is an important stage of their physical, emotional and social development. In the context of teaching ballroom dancing for children 3-4 years old, it is necessary to form the foundations of dance culture that takes into account the age characteristics of children, which involves not only mastering the technical aspects of dance, but also developing emotional expressiveness, coordination of movements, as well as forming the ability to communicate and cooperate within the framework of the dance process. In this regard, special attention should be paid to the use of pedagogical methods that provide an optimal combination of physical development and emotional involvement of children. The purpose of the article is to scientifically substantiate and practically implement the game method of forming initial ballroom dancing skills in children 3-4 years old, which includes the use of fairy-tale plots, game tasks and rhythmic exercises to form dance skills and emotional involvement of children. The research methodology is based on the application of an interdisciplinary approach that combines pedagogical, psychological and choreographic aspects to develop a methodology for teaching ballroom dancing for children aged 3-4. The main method is pedagogical analysis, which allowed us to determine the theoretical foundations of early choreographic training. The observation method was used to study the emotional and physical reactions of children during classes. The comparative analysis method was used to assess the effectiveness of traditional and game approaches to teaching ballroom dancing for children aged 3-4. The research used a modeling method, with the help of which our own game methodology for teaching ballroom dancing for children aged 3-4 was developed. The results of the study revealed the high effectiveness of the game methodology for teaching ballroom dancing for children aged 3-4, proposed by Dmitry Kazko. The method, which combines elements of play, sensorimotor development and fairy-tale plots, ensures natural and harmonious mastery of basic dance skills, promotes the development of musicality, coordination, emotional expression and social competencies. This approach allows you to adapt the educational process to the age and psychophysiological characteristics of children, reduces the risk of overload and increases motivation to learn. The practical application of the method contributes to the formation of stable dance technique skills in children, and also has a positive effect on their physical, emotional and social development. As a result of the study, it was found that the implementation of a game method of teaching ballroom dancing for children of early preschool age contributes to the harmonious development of the child, activating their physical, emotional and cognitive resources. It was determined that taking into account the psychophysiological characteristics of children 3-4 years old requires the adaptation of pedagogical techniques to their level of development, where the game plays a leading role as the main form of educational activity. It is worth noting that Dmytro Kazko's method of teaching ballroom dancing to children aged 3-4 contributes to effective socialization, development of motor skills and emotional growth of children, stimulating their natural need for movement and creativity.